Foundations of Islamic antidrug abuse education - Syed Osman Idid, Syed Zahir Idid; Hashi, Abdurezak Abdulahi (The International Institute of Islamic Thought, 2012)
Among the basic objectives of the Islamic SharÊ‘ah is to protect the human life and human intellect ‒ as such, the consumption of mind-altering and intoxicative substances is prohibited in Islam. Furthermore, Islam imposes criminal penalties on those who consume intoxicative substances such as wine. Muslim jurists (fuqahā) have provided descriptive accounts on the foundations of the Islamic antidrug abuse teachings, categories of mind-altering substances, and preventive laws. They a so identified three categories of mind-altering substances: al-muskirāt, al-mukhaddirāt, and al-muftiraāt. This paper aims to explore the rationale and jurisprudential foundations of Islamic antidrug abuse education. While highlighting the philosophical background of the Islamic antidrug teachings, the paper presents the jurisprudential foundations of the legal penalties for drug abusers. The Qur’ānic terms and the Prophetic statements related to the subject will be referred to, while the opinions of Muslim jurists and theologians on the subject will be unveiled.